2014
DOI: 10.1155/2014/918586
|View full text |Cite
|
Sign up to set email alerts
|

Multiswitching Synchronization of a Driven Hyperchaotic Circuit Using Active Backstepping

Abstract: An active backstepping technique is proposed for the realization of multiswitching synchronization of periodically forced hyperchaotic Van der Pol-Duffing oscillators. The active backstepping technique is a systematic design approach with recursive procedures that skillfully optimizes the choice of Lyapunov functions and active control technique. Using the active backstepping technique, the usual master-slave synchronization scheme is extended to study the synchronization of systems with different combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Theorem 1. Time-delay systems (1), (2), (4), and (5) will achieve asymptotically stable dual multiswitching combination synchronization with systems (7) and (8) for the controllers defined by (15).…”
Section: Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem 1. Time-delay systems (1), (2), (4), and (5) will achieve asymptotically stable dual multiswitching combination synchronization with systems (7) and (8) for the controllers defined by (15).…”
Section: Stability Analysismentioning
confidence: 99%
“…An additional and noteworthy feature of multiswitching was investigated by Ucar in 2008, when multiswitching synchronization was achieved for identical systems. Later, the problem of multiswitching synchronization via adaptive control and active backstepping method has also been investigated. The discussion of aforementioned multiswitching synchronization was restricted to 1 drive and 1 response systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Ucar et al [23] proposed the multiswitching synchronization of chaotic systems, in which the slave system's state variables synchronizes with different state variables of the driver. Despite its clear relevance to information security, only a few studies have been dedicated to this kind of synchronization to-date [4] [24] − [29].…”
Section: Introductionmentioning
confidence: 99%
“…This form of synchronization was proposed by Ucar et al [33] based on active control formalism. Despite its clear relevance to information security, only a few studies of this kind of synchronization have been reported [34][35][36][37][38][39][40]. To the best of our knowledge, all the work on multiswitching synchronization of this kind reported in the literature have related to single-driver/single-response systems.…”
Section: Introductionmentioning
confidence: 99%